Screening of acid- and protease-producing Staphylococcus from Cupei of bran vinegar and optimization of enzyme production conditions - TONG Wenhua, WANG Shuqin, YANG Ying, HUANG Zhijiu, HUANG Dan, LUO Huibo, QIAO Zongwei (Zhongguo niangzao)
In order to improve vinegar flavor, the both acid- and protease-producing strain was separated and screened from the Cupei of bran vinegar by transparent circle method and HPLC. The strain was identified by morphological observation and molecular biology technique, the safety, optimal growth conditions and protease production conditions were investigated, and the strains were applied to solid-state fermented vinegar. The results showed that a strain produced both acid and protease was selected (numbered as D-6), identified as Staphylococcus epidermidis, without pathogenicity. The optimal growth conditions were as follows: culture temperature 37 ℃, pH 5.5, ethanol volume fraction 0.5%, glucose content 3%.The optimum conditions for protease production were as follows: culture temperature 36 ℃, inoculum 4%, culture time 41 h. Under the optimized conditions, the protease activity was 36.12 U/g, which was 49.25%% higher than that before optimization. When it was applied to solid-state fermented vinegar, the contents of total acid, amino acid nitrogen, acetic acid and lactic acid were increased, and the contents were 0.95 mmol/10 g, 0.21 g/100 g, 182.2 mg/L, and 1 472.6 mg/L, respectively.